Actors, Audiences, and Emotions in the Eighteenth Century Communities of Sentiment - McGillivray, Glen. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
'The behavior of people in theaters of the eighteenth century still presents us with a puzzle: why the effusive emotion? In this brilliant study, drawing on a wealth of source material, the emotional style which peaked in Sentimentalism is explained through a deep historical ethnography of the emotional practices of the age. Glen McGillivray attends to both actors' and audiences' performances of feeling, as well as the space in which they were executed, to provide a full picture of what was going on in early modern English theaters.' -Monique Scheer, University of Tübingen, Germany This book offers an innovative account of how audiences and actors emotionally interacted in the English theatre during the middle decades of the eighteenth century, a period bookended by two of its stars: David Garrick and Sarah Siddons. Drawing upon recent scholarship on the history of emotions, it uses practice theory to challenge the view that emotional interactions between actors and audiences were governed by empathy. It carefully works through how actors communicated emotions through their voices, faces and gestures, how audiences appraised these performances, and mobilised and regulated their own emotional responses. Crucially, this book reveals how theatre spaces mediated the emotional practices of audiences and actors alike. It examines how their public and frequently political interactions were enabled by these spaces. Glen McGillivray is Associate Professor in Theatre and Performance Studies at the University of Sydney, Australia. He was an associate investigator with the Australian Research Council Centre of Excellence for the History of Emotions, and his research focuses on the intersection between emotions and performance.
1. Introduction -- 2. Playing to Type -- 3. Communicating Emotions: The Arts of the Actor -- 4. Regulating and Mobilizing Emotions: The Audience -- 5. Mediating Emotions: Practicing Emotions in Place -- 6. Conclusion.
Keywords: Great Britain -- History; Civilization -- History; Social history; Theater -- History; History of Britain and Ireland; Cultural History; Social History; Theatre History